Molecular Characterization of Some Selected Landrace Green Bean (Phaseolus vulgaris L.) Genotypes - Ahmet Onus; Kamile Ulukapı (Journal of Agricultural Sciences)
Molecular markers are widely used to investigate the genetic diversity among bean species. This study was conducted to reveal the molecular characterization of 33 dwarf green bean landraces selected by Karadeniz Agricultural Research Institute. Genotypes were evaluated using Sequence Characterized Amplified Region (SCAR) and Simple Sequence Repeat (SSR) markers. Approximately 73% of the SSR markers gave polymorphic bands and the polymorphism information content (PIC) was between 0.047 and 0.373. All of the SCAR markers were polymorphic and the PIC showed variation from 0.071 to 0.379. Genetic similarity index among green bean genotypes varied between 0.52 and 0.98. Principle coordinate analysis indicated that genetic diversity among the genotypes was not high and all selected genotypes had a close genetic relationship with Andean gene pool.